1993
DOI: 10.1017/s0022215100122352
|View full text |Cite
|
Sign up to set email alerts
|

The mini-grommet and tympanosclerosis: results at two years

Abstract: One hundred and sixteen children with otitis media with effusion (OME) underwent surgery with grommet insertion. A conventional Shah grommet was used in one ear, and a Mini-Shah grommet in the other. Final review of the subjects two years after surgery revealed a significantly lesser degree of tympanosclerosis in the ear into which the Mini-Shah grommet had been inserted. This benefit might have resulted from the lesser mass of the mini-tube or its shorter duration in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Lesser (Lesser et al, 1988) demonstrated that sites of shear stress in the tympanic membrane correlated with the areas likely to develop tympanosclerosis and suggested that a grommet of reduced mass might be beneficial. This was confirmed by our subsequent studies of mini-grommets (Hampal et al, 1991;Dingle et al, 1993). Unfortunately mini-grommets are less well retained than conventional tubes and a reduced tympanosclerosis rate was offset by earlier extrusion of the grommet and earlier recurrence of OME.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Lesser (Lesser et al, 1988) demonstrated that sites of shear stress in the tympanic membrane correlated with the areas likely to develop tympanosclerosis and suggested that a grommet of reduced mass might be beneficial. This was confirmed by our subsequent studies of mini-grommets (Hampal et al, 1991;Dingle et al, 1993). Unfortunately mini-grommets are less well retained than conventional tubes and a reduced tympanosclerosis rate was offset by earlier extrusion of the grommet and earlier recurrence of OME.…”
Section: Discussionsupporting
confidence: 53%
“…Research has suggested that tympanosclerosis confined to the tympanic membrane has no significant adverse effect upon hearing (Tos and Stangerup, 1989;Dawes et al, 1991;Dingle et al, 1993) but only very long term studies would be totally reassuring. Any modification to grommet design which avoids tympanosclerosis but allows prolonged intubation seems desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Placed tubes are extruded by epithelial migration, However, a tube retained for a long time that fails to extrude naturally can cause infection, peritubal TM atrophy and permanent TM perforation [19]. Guidelines for placement of tympanostomy and intentional removal for problematic situations are relatively clear [20], but opinions on the appropriate duration of intubation vary [21][22][23] with no clear guidelines exist for the optimal time to remove asymptomatic tubes that do not cause any of the complications. Our prospective study was intended to provide a guideline based on clinical data for deciding when to remove the T-tubes.…”
Section: Change Of Conductive Hearing Loss According To Intubation Dumentioning
confidence: 99%
“…Many different tympanostomy tubes have been developed with different sizes, shapes, compositions, and coatings. Dingle et al 11 analyzed grommet composition and size as a factor influencing the development of TS after ventilation tube insertion and found that the size or material of the tube did not significantly affect the development of TS. Kinnari et al 12 used albumin‐coated tympanostomy tubes in their clinical study.…”
Section: Discussionmentioning
confidence: 99%